Disseminated Abdominal Hydatidosis: A Rare Presentation of Common Infectious Disease. (8th July 2014) - Almalik, Abdulrahman; Alsharidi, Aynaa; Al-Sheef, Mohammed; Enani, Mushirah
Abstract : Hydatid disease is one of the most geographically widespread zoonoses with substantial disease burden. In this report we are discussing an unusual case of intra-abdominal HD that was ongoing for 22 years despite two surgical interventions. Significant symptomatic relief was achieved within the first two months of combination therapy with albendazole and praziquantel. HD is still of public health concern in the Middle East that needs optimized care.